Diagnosis of an Intraventricular Cyst Using Point-of-Care Cranial Ultrasound in the Pediatric Emergency Department. Issue 3 (March 2017) - Doctor, Kaynan; Cohen, Joanna S.
Abstract : Abstract: A 2-month-old previously healthy male infant presents with 2 days of unusual eye movements and increased fatigue. During evaluation in the pediatric emergency department, point-of-care cranial ultrasound identified a cyst-like mass. Subsequent magnetic resonance imaging confirmed the presence of a cyst within the third ventricle causing obstructive hydrocephalus.